Intention in Articulation: Articulatory Timing in Alternating Consonant Sequences and Its Implications for Models of Speech Production - Marianne, Pouplier (2010)
Several studies have reported that during the production of phrases with alternating consonants (e.g., top cop), the constriction gestures for these consonants can come to be produced in the same prevocalic position. Since these coproductions occur in contexts that also elicit segmental substitution errors, the question arises whether they may result from monitoring and repair, or whether they arise from the architecture of the phonological and phonetic planning process. This paper examines the articulatory timing of the coproduced gestures in order to shed light on the underlying process that gives rise to them. Results show that overall at movement onset the gestures are mostly synchronous, but it is the intended consonant that is released last. Overall the data support the view that the activation of two gestures is inherent to the speech production process itself rather than being due to a monitoring process. We argue that the interactions between planning and articulatory dynamics apparent in our data require a more comprehensive approach to speech production than is provided by current models.